The road to RoboCup 2050. - Burkhard, H.D.
The ultimate goal of the RoboCup initiative is stated as follows: by mid-21st century, a team of fully autonomous humanoid robot soccer players shall win the soccer game, comply with the official rule of the FIFA, against the winner of the most recent World Cup. The authors consider this goal from the perspective of how close we are to it and what has to be done to reach it
Keywords: RoboCup competition; Autonomous humanoid robot; Human-like behavior; Research issues; Soccer playing robots